Barriers and Facilitators to Walking and Physical Activity Among American Indian Elders - Craig N. Sawchuk, PhD; Joan E. Russo; Andy Bogart, MA; Steve Charles; Jack Goldberg, PhD; Ralph Forquera; Peter Roy-Byrne, MD; Dedra Buchwald, MD (Centers for Disease Control and Prevention, 2011)
IntroductionPhysical inactivity is common among older American Indians. Several barriers impede the establishment and maintenance of routine exercise. We examined personal and built-environment barriers and facilitators to walking and physical activity and their relationship with health-related quality of life in American Indian elders.MethodsWe used descriptive statistics to report barriers and facilitators to walking and physical activity among a sample of 75 American Indians aged 50 to 74 years. Pearson correlation coefficients were used to examine the relationship between health-related quality of life and barriers to walking and physical activity after adjusting for caloric expenditure and total frequency of all exercise activities.ResultsLack of willpower was the most commonly reported barrier. Elders were more likely to report personal as opposed to built-environment reasons for physical inactivity. Better health and being closer to interesting places were common walking facilitators. Health-related quality of life was inversely related to physical activity barriers, and poor mental health quality of life was more strongly associated with total barriers than poor physical health.ConclusionWe identified a variety of barriers and facilitators that may influence walking and physical activity among American Indian elders. More research is needed to determine if interventions to reduce barriers and promote facilitators can lead to objective, functional health outcomes.